Calcite growth in Cissus quadrangularis plant extract, a traditional Indian bone-healing aid - Sanyal, A.; Ahmad, Absar; Sastry, M. (Current Science, 2005)
Cissus quadrangularis, a plant that has been customarily used in the Indian subcontinent to hasten the process of healing in bone fractures, has been studied and exploited to synthesize calcite crystals. The plant extract serves as a rich source of calcium ions, which when reacted with CO2, leads to the formation of calcite crystals of highly irregular morphology indicating that bioorganic molecules present in the extract modulate the crystal morphology.
Keywords: bone fracture; calcite crystals; Cissus quadrangularis; traditional healing

Controlling the optical properties of lemongrass extract synthesized gold nanotriangles and potential application in infrared-absorbing optical coatings - Shankar, S. S.; Rai, A.; Ahmad, Absar; Sastry, M. (Chemistry of Materials, 2005)
Anisotropic metal nanoparticles have distinct optical behavior when compared with their spherical counterparts. In this report, we demonstrate a simple method involving the reduction of aqueous gold ions by the extract of the lemongrass plant leading to the formation of gold nanotriangles with interesting absorption in the near-infrared (NIR) region of the electromagnetic spectrum. We show that, by simple variation of the experimental conditions, it is possible to vary the size of the gold nanotriangles and, thus, to tune the absorbance of flat gold nanoparticles in the NIR region. The NIR absorption of the gold nanotriangles is expected to be of application in hyperthermia of cancer cells and in IR-absorbing optical coatings. We show that the lemongrass extract synthesized gold nanotriangles can be easily cast in the form of films on glass substrates and that these films are highly efficient in absorbing IR radiation for potential architectural applications.

CdS quantum dots: enzyme mediated in vitro synthesis, characterization and conjugation with plant lectins - Ansary, Abu Ayoobul; Kumar, S. Anil; Krishnasastry, M. V.; Abyaneh, Majid Kazemian; Kulkarni, Sulabha K.; Ahmad, Absar; Khan, Mohammad Islam (Journal of Biomedical Nanotechnology, 2007)
This paper presents the in vitro synthesis of CdS quantum dot nanoparticles using sulphite reductase and capping peptide in the presence of a co-factor alpha-NADPH, their characterization and conjugation with plant lectins, Jacalin and Chick pea lectin. Incubation of sulphite reductase with aqueous CdCl2, Na2SO3, and capping peptide in the presence of a-NADPH, which acts as a co-factor, resulted in the formation of CdS nanoparticles of dimensions 5-20 nm. These CdS nanoparticles were conjugated with plant lectins by EDAC mediated coupling. These observations are of significance, as it will help in the development of eco-friendly process for the formation of CdS nanoparticles and their application as fluorescent biolabels. Moreover the above studies will also help in designing a rational enzymatic strategy for the synthesis of nanomaterials of different chemical composition, shapes and sizes as well as their separation.
Keywords: bio-label; CdS quantum dots; conjugation; Enzyme; in vitro synthesis; Nanoparticles

Chemical, thermal and pH-induced equilibrium unfolding studies of fusarium solani lectin - Khan, Feroz; Ahmad, Absar; Khan, Mohammad Islam (IUBMB Life, 2007)
The effect of urea, guanidine thiocyanate, temperature and pH was studied on the conformational stability of Fusarium solani lectin. Equilibrium unfolding with chemical denaturants showed that the lectin was least stable at pH 12 and maximally stable at pH 8.0 near its pI ( 8.7). Guanidine thiocyanate ( the concentration of denaturant at which the protein is half folded, D-1/2 = 0.49 M at pH 12) was found to be an eight times stronger denaturant than urea (D-1/2 = 3.88 M at pH 12). The unfolding curves obtained with fluorescence and CD measurements showed good agreement indicating a monophasic nature of unfolding and excluded the possibility of formation of any stable intermediate. The effect of pH on the lectin was found to be unusual as at acidic pH, the lectin showed a flexible tertiary structure with pronounced secondary structure, and retained its hemagglutinating activity. On the other hand, the lectin did not show any loss of conformation or activity upto 70 degrees C for 15 min. Moreover, thermal denaturation did not result in the aggregation or precipitation of the protein even at high temperatures. Thermal denaturation was also carried out in the presence of a low concentration of guanidine thiocyanate. Change in the enthalpy of transition (Delta H-m) varied linearly with transition temperature (T-m), which indicated that the heat capacity (Delta C-p =3.95 kJ (.) mol(-1) (.) K-1) of the lectin remained constant during the unfolding.
Keywords: Denaturation; Fusarium solani; guanidine; Lectin; thermal; Unfolding

Complex carbohydrate specificity of lectin from fruiting body of ganoderma lucidum. a surface plasmon resonance study - Thakur, Atul; Pal, Lakhan; Ahmad, Absar; Khan, Mohammad Islam (IUBMB Life, 2007)
The thermodynamics and kinetics of binding of glycans and glycoproteins to Ganoderma lucidum lectin was studied using surface plasmon resonance. The lectin showed highest affinity for asialo triantennary N glycan (Ka = 3.52 x 10(5)) among the glycans tested. There was a several fold increase in affinity for glycoproteins compared to their corresponding glycans and coincident increase in contribution from enthalpy (Delta H), suggesting the involvement of hydrogen bonding in the interaction as well as involvement of protein-protein interactions. Increased affinity also showed increase in unfavorable negative binding entropy (Delta S) which was compensated with higher enthalpy. The glycoproteins showed faster association rates (k(1)) and the activation energy (E-1(double dagger)) in the association process was much lower for the glycoproteins than glycans, resulting in their faster associations. These observations elaborate the role of protein matrix in lectin-glycoconjugate interaction.
Keywords: ganoderma lucidum; glycans; Lectin; SPR